Safety profile of pneumococcal conjugate vaccines: systematic review of pre- and post-licensure data - Frank DeStefano; Dina Pfeifer; Hanna Nohynek
A 7-valent pneumococcal polysaccharide-protein conjugate vaccine (PCV7) was licensed in the United States of America in 2000, but no comprehensive postmarketing review of safety has been carried out. We conducted a systematic review of the safety of PCV7 and other pneumococcal conjugate vaccines. A total of 42 studies were included in the review. Reactogenicity data from some randomized trials suggest that PCV7 may result in more local reactions and fever than certain comparison vaccines. However, the reactions were mild and self-limited, and PCV7 did not carry an increased risk of severe injection-site reactions or high fever. Some, although not all, of the randomized trials in children found that mild local and systemic reactions associated with PCV7 may increase with the number of doses, at least over the three-dose primary series. In addition, PCV7 and other pneumococcal conjugate vaccines were found to have tolerable reactogenicity in Native American and African populations and in medically high-risk groups for which pneumococcal vaccination is recommended. Two of the largest studies of PCVs, one involving PCV7 and the other, PCV9, found a statistically significant increased risk of hospitalization for reactive airway disease, including asthma. Another large trial of PCV9, however, did not find an increased risk of asthma. In conclusion, this review of the evidence did not identify any major safety problems with PCV7 or any other pneumococcal conjugate vaccine, with the possible exception of reactive airway disease, which may bear further scrutiny as additional data become available.